Level and Factors of Womenâ€™s Employment in the Sekhukhune District in the Limpopo Province of South Africa: Some Discriminant Analysis - Kyei, Kwabena A. (Journal of Economics and Behavioral Studies, 2015)
Unemployment is very high in South Africa with the official rate ranging from 26.7% to 35%. The Limpopo province has the highest proportion of rural dwellers in South Africa and possibly higher unemployment rate than the national average. Womenâ€™s unemployment is a much bigger problem especially when women are the bread winners. Most women singularly look after their children due to polygamy and / or labour migrant system which usually takes the men from home to other parts of the country. This study focuses on factors which militate against womenâ€™s employment. A 3-stage sample survey was conducted between May 2013 and January 2014 covering all the municipalities in the Sekhukhune district. About 2000 women aged between 20 and 55 years were interviewed. Applying discriminant analysis, this study shows that over 85% of the women in the district are unemployed; and factors like: education, age, family status and marital status affect the employment status of women in Sekhukhune. DA = 0.734educ + 0.654age +0.490familystatus + 0.153marital status If Limpopo wants to reduce unemployment of women and to redress familyâ€™s crises, this study recommends that efforts be made to â€œeducateâ€ women, i.e. encourage women to complete higher/ tertiary education and also be given special preference/family support in job offers.